2018
DOI: 10.1111/ijpp.12485
|View full text |Cite
|
Sign up to set email alerts
|

Differences in UK healthcare professionals’ knowledge, attitude and practice towards infliximab and insulin glargine biosimilars

Abstract: Healthcare professionals were more comfortable with the initiation of biosimilars than switching current patients. Medical consultants/registrars and pharmacists were more informed than nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 5 publications
2
21
0
Order By: Relevance
“…After screening for eligibility, we included 16 studies in the analysis ( Table 2 ) [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. The included studies were from Europe, UK, United States, Australia, Asia, and Africa [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. The targeted healthcare professionals were: clinicians, GPs, pharmacists, nurses, consultants, care managers, and specialists in clinical settings where biologics are more involved such as oncology, rheumatology, endocrinology, gastroenterology, dermatology, nephrology, and hematology.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After screening for eligibility, we included 16 studies in the analysis ( Table 2 ) [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. The included studies were from Europe, UK, United States, Australia, Asia, and Africa [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. The targeted healthcare professionals were: clinicians, GPs, pharmacists, nurses, consultants, care managers, and specialists in clinical settings where biologics are more involved such as oncology, rheumatology, endocrinology, gastroenterology, dermatology, nephrology, and hematology.…”
Section: Resultsmentioning
confidence: 99%
“…In seven studies [ 21 , 22 , 27 , 29 , 31 , 33 , 34 ], we found that healthcare professionals had a good knowledge of biosimilars, and at least know the basic concepts of them. However, healthcare professionals were not satisfactorily familiar with concepts and the processes of interchangeability, extrapolation and pharmacovigilance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…19 23 32 The main experienced advantages of biosimilars are cost savings, 18 22-25 31 lower price in comparison with the originator biologic medicine 31 38 and the possibility to get experience with the new product 28 29 (table 2). In addition, single studies reported that robust pharmacovigilance studies, 18 easier access to treatment for patients, 31 and approval of the European Medicines Agency or the Food and Drug Administration 38 were motivators for prescribing biosimilars. The most commonly reported Open access disadvantages were distrust in safety, 10 18 22 31 efficacy, 10 18 22 31 33 immunogenicity 10 25 31 and indication extrapolation of biosimilars 10 34 or the lack of clinical data on biosimilars.…”
Section: Self-rated and Measured Knowledge On Biosimilars And Sourcesmentioning
confidence: 99%
“…In addition, biosimilar use is regularly tracked by NHS Scotland as part of national therapeutic indicators ( NHS Scotland, 2017 ). These various regional and national activities can help address concerns among healthcare professionals, especially regarding switching ( Aladul et al., 2018 ; Aladul et al., 2019 ), with NHS England currently aiming for 90% of new patients to be prescribed the best-value biological medicine within 3 months of the launch of a biosimilar as well as actively encouraging switching ( NHS England, 2017a ) to meet the goal of an 80% biosimilar prescription rate within one year ( Davio, 2018 ). NHS England has also invested in many educational activities ( NHS England, 2015 ; NHS England, 2017b ; NHS England, 2019a ) and closely monitors local adoption of biosimilars through regional teams that facilitate implementation of national policy measures ( NHS England, 2019b ).…”
Section: Introductionmentioning
confidence: 99%